2004
DOI: 10.1016/j.femsle.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on the Ebola virus matrix protein VP40 indicate that matrix proteins of enveloped RNA viruses are analogues but not homologues

Abstract: Matrix proteins are the driving force of assembly of enveloped viruses. Their main function is to interact with and polymerize at cellular membranes and link other viral components to the matrix-membrane complex resulting in individual particle shapes and ensuring the integrity of the viral particle. Although matrix proteins of different virus families show functional analogy, they share no sequence or structural homology, Their diversity is also evident in that they use a variety of late domain motifs to comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…Despite functional and structural homology with VP40, membrane binding modes appear to differ significantly between the 2 viruses. VP40 has been observed in multiple oligomeric forms; oligomerization occurs via the N-terminal domain to form monomeric, dimeric, hexameric, and octameric species (10,17,18,(30)(31)(32). In contrast, BDV-M has been observed in only 2 oligomeric states (15,16), namely tetramers and octamers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite functional and structural homology with VP40, membrane binding modes appear to differ significantly between the 2 viruses. VP40 has been observed in multiple oligomeric forms; oligomerization occurs via the N-terminal domain to form monomeric, dimeric, hexameric, and octameric species (10,17,18,(30)(31)(32). In contrast, BDV-M has been observed in only 2 oligomeric states (15,16), namely tetramers and octamers.…”
Section: Discussionmentioning
confidence: 99%
“…These M-proteins exhibit neither sequence nor structural homology to one other (10). Here, we report the 3D structure of BDV-M, a full-length M-protein structure of a nonsegmented NSV, and show that the peripheral membrane protein binds ssRNA oligonucleotides.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…A number of matrix-like proteins are known to bind membranes or lipid vesicles in vitro, most likely through a combination of hydrophobic and electrostatic interactions (12)(13)(14). Expression of certain Ms in eukaryotic cells in the absence of other viral proteins can induce formation of virus-like particles (VLPs).…”
mentioning
confidence: 99%
“…Though similar in function, the sequence homology of the M proteins from filo-, rhabdo-, myxo-, and paramyxovirus and retroviral MA do not show clear homology although the L domains of PS/TAP or PY motifs are similar in these proteins that function in budding of virions from host cells (40,79,80,119,216). Comparison of the structural homology has been examined by structural biologists in reviews of the literature between Ebola virus VP40, VSV M, and HIV MA and these were found to have no structural homology (200), but a comparison between influenza virus M1 and HIV MA and CA proteins revealed that the M1 protein may have a combination of the important structural assembly elements of the MA and CA proteins (77). Taken together these observations show that trying to find the evolutionary link between proteins from RNA viruses is a complicated endeavor.…”
Section: Enveloped Rna Viruses: Origins and M Proteinsmentioning
confidence: 99%